Physics teachers’ perceptions and anxieties about the use of technology-integrated learning resources on magnetic field material: A preliminary research on augmented reality-integrated STEM learning - Widyanti, R; Abdurrahman; Herlina, K; Zahara, M; Agustina, L (Journal of physics. Conference series, 2021)
The educational world development faces the challenges of the 21 st -century where technology plays an important role in learning so that technology-integrated teaching material is needed. The subjects of this study were 48 physics subject teachers in several schools in Lampung province. The research method used was a mixed method. The data was collected using questionnaires and interviews. The results of the study revealed that the teachers have never made learning resources assisted by the integration between STEM and augmented reality technology. The teachers also revealed that they were anxious that the learning resources that they will use cannot fully meet the competency standards if they are not equipped with learning technology that supports the abstract concepts learning. Thus, the teachers expected technology-assisted learning resources in which texts, images, 3D animations, and videos can be integrated. For further researchers, it is necessary to develop STEM learning resources assisted by augmented reality technology.